Zakat Accounting in Supporting the Distribution of Productive Zakat Funds for Business Capital - Tita Kartika (SINTESA, 2022)
This study aims to determine the description of zakat accounting on the empowerment of productive zakat funds for business capital at BAZNAS Kab. Sumedang.The reseach method used for this reseach is descriptive qualitative method, the data collection technique used is the observation method, the interview method includes structure and unstructured interviews and the method of literature study. The results obtained (1) BAZNAS Kabupaten Sumedang uses sharia accounting that is not based on interest (non interest) (2) Sumedang Makmur is one of the programs created by BAZNAS Kabupaten Sumedang in helping SMEs to increase their business by providing interest – free capital loans to mustahiq (3) Zakat Accounting at BAZNAS Kabupaten Sumedang is in accordance with PSAK No.109, and has used PSAK No. 109 since 2012 until now.